PENDAMPINGAN PROGRAM SEKOLAH PENGGERAK UNTUK MENGEMBANGKAN KOMPETENSI GURU MELALUI VBSO - Tanti Sri Kuswiyanti; Fidiatun Adiyan; Vicky Hidantikarnillah; Annisa Fitri Nurjannah (Jurnal Abdimas Bina Bangsa, 2023)
This journal reviews the government's program regarding the assistance of the Sekolah Penggerak program for the development of teacher competence through VBSO. The government makes this program for the education unit level from kindergarten (PAUD), primary school (SD), secondary school (SMP), high school (SMA) and the education unit level Schools with Special Needs. The Program of Sekolah Penggerak focuses on the implementation of Kurikulum Merdeka that applies Students Centered Learning and Differentiated Intructions. The aim of this study is to provide assistance to develop teacher competence through Video Based on Self Observation (VBSO) in three schools assisted by the researchers: SDIT. Science Lantern, SDN. Sukasari 5 & SDN. Bojong 2 in Tangerang City. The method used in this research is observation in which we collect data accompanied by recording of the situation. The result of this study indicates that Students Centered Learning and Differentiated Instruction still need to be improved